If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8senx + -3cosx = 0 Reorder the terms: -3cosx + 8ensx = 0 Solving -3cosx + 8ensx = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-8ensx' to each side of the equation. -3cosx + 8ensx + -8ensx = 0 + -8ensx Combine like terms: 8ensx + -8ensx = 0 -3cosx + 0 = 0 + -8ensx -3cosx = 0 + -8ensx Remove the zero: -3cosx = -8ensx Divide each side by '-3osx'. c = 2.666666667eno-1 Simplifying c = 2.666666667eno-1
| Y+15y+36=0 | | 2x+15=-2x-5 | | -3y-9y=4/5 | | 8x^2-5x-8=0 | | 4(y-9)=-6(5+y) | | 6x-52=3x | | 0.66q+0.75=0.5 | | 4(x+3)=-5 | | 8x+15+3x+20= | | 15+y=2y-7 | | 12/35=6/7n | | 7a+25=60+2a | | -14x=-5x+36 | | s-35=20 | | 30r^3+85r^2-70r= | | 6-(2-4x)+5=3(1-3x) | | 27+4x=7 | | 3x-t=2x | | r+31=-3(1-6r) | | -2(-2x+3)=-10x-8 | | 4x-1=-2x+7 | | 6x+4(-3x-4)=44 | | -2(8-5x)=-126 | | 3x^4+2x-4=0 | | x^2-24x=-35 | | N-/6=20 | | 1.2/y=2.4/3.4 | | 2x^4+2x-4=0 | | 9-7x=-3x-15 | | Z^2-18z=66 | | =2x^2+x-7 | | 24x^4+23x^3+60x^2-125x-500=0 |